The Definition, Characteristics and Development of Malay Poetry - Intan Devira Salsabila; Siti Soleha; Evi Julianti; Citra Aulia Maharani; Maryamah (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe: 1) the character of Malay poetry in the context of culture and literature; 2) the development of Malay poetry over time; 3) the position of Malay poetry compared to other ancient poetry; 4) the relevance of Malay poetry in the modern era. The study was conducted in March–May 2025 in several libraries and classical manuscript documentation centers in Jakarta and Riau; in line with the use of library methods in research. The population in this study was all documented Malay poetry, while the sample was selected purposively based on the diversity of themes and periods of their emergence. The research instruments were in the form of literature study guidelines and text analysis sheets. Research data were collected using non-test instruments, namely observation guidelines and checklists that were compiled objectively and systematically to meet the requirements of a reliable non-test instrument. Research data were analyzed using content analysis methods and a qualitative descriptive approach. The results of the study indicate that: 1) Malay poetry not only functions as literary entertainment, but also as a medium for cultural transmission, preservation of identity, and conveying the values ??of local wisdom; 2) Malay poetry experienced rapid development during the golden age of Malay Islamic kingdoms such as the Sultanates of Aceh, Riau-Lingga, and Johor through Malay literary figures who developed from oral to written literature, especially after the introduction of the Arabic-Malay script and print media; 3) poetry has unique characteristics compared to pantun and gurindam and functions as a more flexible form of discourse; 4) poetry remains relevant in education because it contains moral and religious values that can be taught in the context of character education and cultural literacy in schools and has the potential to be developed in modern media.